Bacteriological Characteristics of Meenachil River, Kottayam, Kerala, South India: A Seasonal Study - Mathew , Sojomon; Radhika , R.; Shiny , K. J. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2023)
The Meenachil River is a major river that runs through different taluks, viz. Meenachil, Vaikom and Kottayam of Kerala, India. The Meenachil River's bacteriological characteristics were investigated. Six Meenachil riverine stations were chosen for the investigation. Bacteriological parameters were studied in three different seasons during 2022: monsoon, postmonsoon, and premonsoon. Estimating bacterial production is a critical step in quantitatively understanding the function and contribution of bacteria in material cycling within given aquatic habitats.TCC and FCC values are high during the pre-monsoon season and low during the post-monsoon season.During pre-monsoon, total Coliform number ranged from 230 MPN/100ml to 1100 MPN/100ml, 93 MPN/100ml to 380 MPN/100ml during post-monsoon, and 149 MPN/100ml to 470 MPN/100 ml during monsoon. Escherichia, Citrobacter, Enterobacter, and Klebsilla are examples of coliform bacteria. The highest value of Coliform was 1100 MPN/100ml at station 1 Poonjar during the pre-monsoon period, and the lowest value was 93 MPN/100ml at station 6 Illikkal during the post-monsoon period. Faecal contamination is seen in all the six stations. The bacteria E.coli, Salmonella sp., Pseudomonas sp., Enterobacter aerogenes, Shigelle sp., Vibrio cholerae, Vibrio parahaemolyticus, Proteus sp., Klebsiella sp., have been isolated from various stations, primarily from stations 1, 2, 3, 4, 5, and 6. During pre-monsoon, station 1 in Pooonjar recorded the highest FCC value of 460 MPN/100 ml, while station 6 in Illikkal recorded the lowest value of 20 MPN/100 ml. Although the current situation is not dire or alarming, the river water needs to be closely monitored in order to improve its quality and allow for better and more sustainable management.